2019
DOI: 10.1038/s41598-019-52802-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimating growth and photosynthetic properties of wheat grown in simulated saline field conditions using hyperspectral reflectance sensing and multivariate analysis

Abstract: The timely estimation of growth and photosynthetic-related traits in an easy and nondestructive manner using hyperspectral data will become imperative for addressing the challenges of environmental stresses inherent to the agricultural sector in arid conditions. However, the handling and analysis of these data by exploiting the full spectrum remains the determining factor for refining the estimation of crop variables. The main objective of this study was to estimate growth and traits underpinning photosyntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 60 publications
(96 reference statements)
1
20
1
Order By: Relevance
“…In this regard, Ma et al [28] reported that saline conditions caused pigment degradation and leaf burning in salt-sensitive species. A suppressed effect of salinity on photosynthetic pigments has been reported in many investigations [3,5,7].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In this regard, Ma et al [28] reported that saline conditions caused pigment degradation and leaf burning in salt-sensitive species. A suppressed effect of salinity on photosynthetic pigments has been reported in many investigations [3,5,7].…”
Section: Discussionmentioning
confidence: 83%
“…e notable decreases were observed with Sakha8, which was the most influenced cultivar by saline conditions, followed by Giza168 and Sakha69 which was the most resistant cultivar to the NaCl salt application. e response of plant growth to salinity stress varies among species and has been reported in many investigations [1,2,5,21,22]. In this consideration, Bacu et al [7] demonstrated that an increase in salt concentration (50, 100, and 200 mM NaCl) induced a significant decrease in the growth criteria (shoot, root, and leaf length) of five wheat cultivars.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, Sakha93 and Misr2 are more recent releases and are also known to be salinity stress-tolerant cultivars [37,38]. In contrast, Sakha61, Sakha94, Gemmiza9 cultivars were previously found to be sensitive to salinity stress [37,39,40]. Furthermore, Giza164 and Gemmiza10, Sides1, and Giza168 were found to be sensitive to moderately tolerant cultivars to salinity stress [8,37,38].…”
Section: Introductionmentioning
confidence: 99%
“…For example, bread wheat tolerance to salinity is characterized by higher K + to Na + uptake [18]. Maintaining a high K/Na ratio is critical in preserving cell volume regulation under salt stress, which is found to increase salt tolerance in wheat [39]. In bread wheat, a locus (Kna1) on the 4D chromosome was found to be associated with Na + accumulation and the K/Na ratio [70].…”
mentioning
confidence: 99%